MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL REALISTIC MATHEMATICS EDUCATION (RME) PADA MATA PELAJARAN MATEMATIKA DI KELAS V SDS SALSA CINTA RAKYAT - Daitin Tarigan; Irsan Rangkuti; Arifin Siregar (FIP Unimed, 2018)
ABSTRACTThe main problem in this study is the low learning outcomes of fifth grade students of Salsa Cinta Rakyat Elementary Elementary School Percut Sei Tuan in fractions material mathematics lessons. This research aims to improve student learning outcomes by using the Realistic Mathematics Education (RME) model on mathematics subjects in the VB class of Salsa Cinta Rakyat Private Elementary School Academic Year 2017/2018. The results of the study can be concluded that the use of the Realistic Mathematics Education (RME) learning model can improve student learning outcomes in mathematics lessons in the fifth grade fractions of Salsa Private Elementary School Love People Percut Sei Tuan Keywords: Learning Outcomes, Models ABSTRAK Permasalahan utama dalam penelitian ini adalah rendahnya hasil belajar siswa kelas V SD Swasta Salsa Cinta Rakyat Percut Sei Tuan pada pelajaran matematika materi pecahan. Penelitian yang dilakukan ini bertujuan untuk meningkatkan hasil belajar siswa dengan menggunakan model Realistic Mathematics Education (RME) pada mata pelajaran pelajaran matematika di kelas VB SD Swasta Salsa Cinta Rakyat Tahun Ajaran 2017/2018. Hasil penelitian dapat disimpulkan bahwa penggunaan model pembelajaran Realistic Mathematics Education (RME) dapat meningkatkan hasil belajar siswa pada pelajaran matematika materi pecahan kelas V SD Swasta Salsa Cinta Rakyat Percut Sei Tuan Kata kunci: Hasil Belajar, Model